Porous ceramic particle, preparation method and application method thereof

High porosity porous ceramic particles are prepared through 3D printing technology and used in cigarette filters, which solves the problem of weak adsorption of existing filters and achieves effective filtration and reduction of harmful components in flue gas.

CN119504284APending Publication Date: 2025-02-25HUBEI CHINA TOBACCO INDUSTRY CO LTD +1

Patent Information

Application Number
CN202411762572.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing cigarette filter has low porosity and small pore size, resulting in weak adsorption force and cannot effectively reduce the content of harmful components in the flue gas.

Method used

Porous ceramic particles are used to prepare photocured slurry through 3D printing technology to form a spherical ceramic blank, remove organic components and sinter them to obtain porous ceramic particles with high porosity, which are used for the preparation of tobacco filters.

Benefits of technology

It significantly improves the filtration effect of total particulate matter, tar and nicotine, reduces the content of harmful substances, and improves the quality of cigarettes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504284A_ABST
    Figure CN119504284A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of porous ceramic particles, which comprises the following steps: (1) preparing a photocuring slurry: mixing and stirring ceramic powder, a photocuring oligomer, a reactive diluent, a photoinitiator and modified silicon oxide according to a weight ratio of (4-5): (3-4): (2-3): (0.05-0.25): (0.1-1) to obtain the photocuring slurry; (2) carrying out 3D printing molding on the photocuring slurry to obtain a spherical ceramic body; (3) treating the spherical ceramic green body, and removing organic matter components in the spherical ceramic green body to form micropores; (4) sintering the treated spherical ceramic green body to obtain porous ceramic particles; wherein the diameter of the porous ceramic particles ranges from 1 mm to 1.5 mm. The porous ceramic particle provided by the invention is of a micro-spherical structure, has relatively large porosity and rich void structures inside, is high in porosity, is used in a tobacco filter tip, and can remarkably improve the filtering effect on total particulate matters, tar and nicotine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cigarette raw materials, and more specifically, to porous ceramic particles, a preparation method and an application method thereof. Background Art

[0002] Most of the components in cigarette smoke are harmful to the human body, such as benzene, 2-aniline, 4-aminobiphenyl, aldehydes, volatile nitrosamines, tobacco-specific nitrosamines, benzopyrene, etc., which are all carcinogens. As a bridge between smokers and smoke, cigarette filters have been widely used in cigarette products because of their strong filtering effect on smoke particulate matter, which can significantly reduce the harm of harmful components in smoke to human health and improve the quality of smoking. The current filter tips are mainly made of acetate fiber (or propylene tow), which can block tar and smoke substances to a certain extent. However, the existing filter tip technology is a simple physical adsorption, which is mainly to maintain the original taste of cigarettes. After the filter tip adsorption, there is still a large amount of smoke tar. To this end, it is necessary to combine better and more advanced filtering technology, as well as cigarette taste and combination technology.

[0003] Patent CN111227302A discloses an adsorption filter bead used in a cigarette filter. The raw materials include nano-tourmaline, hexacyclic stone powder, nano-silver ion material, titanium dioxide, activated carbon and calcium carbonate. The preparation method includes grinding the raw materials, homogenizing and slurrying, preparing wet sample particles, and drying. The adsorption filter bead can realize nano-adsorption filtration of the cigarette filter, reduce tar, and remove fine particles. However, the adsorption filter bead has a low porosity, a small pore size, and an insufficiently rich internal porous structure, resulting in weak adsorption force, and further improvement is still needed. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a method for preparing porous ceramic particles. The prepared porous ceramic particles have large porosity and strong adsorption capacity.

[0005] Furthermore, the present invention also provides porous ceramic particles prepared by the above-mentioned method for preparing porous ceramic particles.

[0006] Furthermore, the present invention also provides a method for using the porous ceramic particles in preparing tobacco filters.

[0007] The technical solution provided by the present invention is as follows: A method for preparing porous ceramic particles comprises the following steps: (1) Preparing a photocurable slurry: mixing and stirring a ceramic powder, a photocurable oligomer, a reactive diluent, a photoinitiator and modified silicon oxide in a weight ratio of (4-5): (3-4): (2-3): (0.05-0.25): (0.1-1) to obtain a photocurable slurry; (2) 3D printing the photocurable slurry to obtain a spherical ceramic body; (3) treating the spherical ceramic body to remove organic components in the spherical ceramic body to form micropores; (4) sintering the treated spherical ceramic body to obtain porous ceramic particles; Wherein, the diameter of the porous ceramic particles is 1-1.5 mm.

[0008] Preferably, the porous ceramic particles have a diameter of 1.2 mm.

[0009] Preferably, the weight ratio of ceramic powder, photocurable oligomer, reactive diluent, photoinitiator and modified silicon oxide in the photocurable slurry of step (1) is (4.01-4.98): (3.12-3.87): (2.2-3): (0.051-0.24): (0.1-0.98).

[0010] In the step (1) photocurable slurry, the weight ratio of ceramic powder, photocurable oligomer, reactive diluent, photoinitiator and modified silicon oxide is 4.46:3.67:2.61:0.061:0.45.

[0011] The ceramic powder is aluminum oxide with a purity of more than 99.9%, and the D50 of the ceramic powder is 4 μm-10 μm. Preferably, the D50 of the ceramic powder is 0.5 μm-10 μm.

[0012] Wherein, the ceramic powder is aluminum oxide with a purity of more than 99.9%, and the D50 of the ceramic powder is 4 μm-10 μm, preferably, 5 μm-10 μm.

[0013] Wherein, the photocurable oligomer is a modified epoxy acrylate oligomer, which is prepared by the following method: Step 1-1, add 36-38.6 parts of epoxy resin and 16-19 parts of solvent, stir to dissolve and heat to 105°C-120°C; Step 1-2, add 7.2-9.7 parts of long-chain alkyl ester from biological sources, stir evenly, add 0.58-0.9 parts of triphenylphosphine, and react at a temperature of 115° C.-125° C. for 2-3 hours; Step 1-3, the temperature is controlled between 105°C and 108°C, 2.1-3.3 parts of hard monomer, 3.3-4.2 parts of soft monomer, 6.7-7.2 parts of functional acrylic monomer, and 0.51-0.58 parts of initiator are mixed evenly, and added dropwise at a uniform speed for 2-3 hours. After the reaction is completed, keep warm for 2 hours, cool to below 50°C and discharge the material to obtain a modified epoxy acrylate oligomer.

[0014] Wherein, the long-chain alkyl ester with biological origin is selected from one or more of cardanol acrylate, allyl glycidyl cardanol ether, glycidyl methacrylate cardanol ether, hydroxyethyl acrylate cardanol ether or lauryl methacrylate; and / or, the hard monomer is selected from one or more of methacrylic acid, methyl methacrylate or vinyl acetate; And / or, the soft monomer is butyl acrylate or butyl methacrylate; And / or, the functional acrylic monomer is methoxy polyethylene glycol acrylate; And / or, the solvent is a water-soluble alcohol ether solvent, selected from one or more of ethylene glycol butyl ether, butanol, isopropanol, sec-butanol, and ethanol; And / or, the initiator is a peroxide and / or an azo initiator, selected from one or more of benzoyl peroxide, tert-butyl hydroperoxide, tert-butyl perbenzoate, di-tert-butyl peroxide, and azobisisobutyronitrile.

[0015] Wherein, the molecular weight of the methoxy polyethylene glycol acrylate is 550-1000, preferably 550, 600, 750, 1000.

[0016] Wherein, the reactive diluent is selected from one or more of dimethacrylate, trimethacrylate, tetramethacrylate, diisoacrylate, trimethacrylate or triisoacrylate; And / or, the photoinitiator is one or more of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, bisbenzoylphenylphosphine oxide, and α-dimethoxy-α-phenylacetophenone.

[0017] The modified silicon oxide is nano silicon oxide coated with starch, which is prepared by the following method: starch is configured into a starch aqueous solution with a concentration of 10-20wt%, nano silicon oxide is added into the starch aqueous solution, stirred evenly so that the nano silicon oxide is fully coated with starch, and the modified silicon oxide is obtained after drying and grinding, wherein the weight ratio of the nano silicon oxide to the starch aqueous solution is 1:10-15.

[0018] The specific method of 3D printing the photocurable slurry in step (2) is as follows: the three-dimensional model of the porous ceramic particles is introduced into a 3D printing device to prepare a spherical ceramic body. The 3D printing device can be a pull-up type or a sinking type photocurable ceramic 3D printer according to the needs.

[0019] Wherein, the step (3) comprises the following steps: heating to 450°C-600°C at a heating rate of 0.1°C / min-10°C / min, and keeping the temperature for 0.5h-10h.

[0020] The sintering step in step (4) comprises: heating to 1650°C-1850°C at a heating rate of 0.5°C / min-20°C / min, and keeping the temperature for 0.5h-10h.

[0021] A porous ceramic particle prepared by the preparation method as described above, wherein the porosity of the porous ceramic particle is 71.4%-77.8%.

[0022] A method for using the porous ceramic particles prepared by the above preparation method in preparing tobacco filters: the porous ceramic particles and acetate fiber bundles are formed into filter rods.

[0023] Wherein, the application method is that the doping amount of porous ceramic particles accounts for 15% of the total volume of porous ceramic particles and acetate fiber bundles.

[0024] Compared with the prior art, the present invention provides a method for preparing porous ceramic particles, comprising the following steps: (1) preparing a photocurable slurry: mixing and stirring ceramic powder, photocurable oligomer, active diluent, photoinitiator and modified silicon oxide in a weight ratio of 4-5:3-4:2-3:0.05-0.25:0.1-1 to obtain a photocurable slurry; (2) 3D printing the photocurable slurry to obtain a spherical ceramic body; (3) treating the spherical ceramic body to remove organic components in the spherical ceramic body to form micropores; (4) sintering the treated spherical ceramic body to obtain porous ceramic particles; wherein the porous ceramic particles have a diameter of 1-1.5 mm. The porous ceramic particles of the present invention are microspherical structures, have a large porosity and rich void structure inside, have a high porosity, and are used in tobacco filters to significantly improve the filtering effect of total particulate matter, tar and nicotine. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 A 3D printing model diagram and size diagram of the porous ceramic particles according to an embodiment of the present invention; Figure 2This is a 3D printing model diagram of the porous ceramic particles according to an embodiment of the present invention. DETAILED DESCRIPTION

[0027] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention are clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0028] It should be noted that when an element is referred to as being "fixed on" or "set on" another element, it can be directly on the other element or indirectly set on the other element; when an element is referred to as being "connected to" another element, it can be directly connected to the other element or indirectly connected to the other element.

[0029] It should be understood that the terms "length", "width", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside" and "outside" etc., indicating the orientation or position relationship, are based on the orientation or position relationship shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0030] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" and "several" is two or more, unless otherwise clearly and specifically defined.

[0031] It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with this technology. They are not used to limit the conditions under which the present invention can be implemented, and therefore have no substantive technical significance. Any structural modification, change in proportion or adjustment of size, without affecting the effects and purposes that can be achieved by the present invention, should still fall within the scope of the technical contents disclosed by the present invention.

[0032] The embodiments of the present invention are written in a progressive manner.

[0033] Material source Ceramic powder: Sumitomo Chemical AM series high purity alumina; Dimethacrylate: commercially available; Trimethacrylate: commercially available; Diisoacrylate: commercially available; Triisoacrylate: commercially available; 2-Hydroxy-2-methyl-1-phenylpropanone: commercially available; 1-Hydroxycyclohexylphenyl ketone: commercially available; 2,4,6-Trimethylbenzoyl-diphenylphosphine oxide: commercially available; Bisbenzoylphenylphosphine oxide: commercially available; Nano silicon oxide: commercially available, CAS No. 60676-86-0; Silicon oxide: Sumitomo Chemical AM-21; Lauryl methacrylate: commercially available; Methacrylic acid: commercially available; Methyl methacrylate: commercially available; Vinyl acetate: commercially available; Butyl acrylate: commercially available; Butyl methacrylate: commercially available; Butyl acrylate: commercially available; Methoxy polyethylene glycol acrylate: commercially available; Azobisisobutyronitrile: commercially available; Starch: commercially available CAS number 9005-25-8; 3D printer model: BlackChuang Technology Rocket 1.

[0034] Example 1 A method for preparing porous ceramic particles comprises the following steps: (1) Preparing a photocurable slurry: preparing 446 g, 367 g, 261 g, 6.1 g, and 45 g of a ceramic powder, a photocurable oligomer, a reactive diluent, a photoinitiator, and modified silicon oxide, respectively, mixing and stirring them to obtain a photocurable slurry; (2) importing the three-dimensional model of the porous ceramic particles into a 3D printing device, and 3D-forming the photocurable slurry obtained in step (1) to obtain a spherical ceramic body. The 3D printing device is a sinking photocurable ceramic 3D printer; (3) treating the spherical ceramic body by heating it to 550°C at a heating rate of about 5°C / min and keeping it at that temperature for 2 hours to remove the organic components in the spherical ceramic body to form micropores; (4) Sintering the treated spherical ceramic body, heating it to 1700°C at a heating rate of about 10°C / min, and keeping it at that temperature for 2 hours to obtain porous ceramic particles, such as Figure 1 , Figure 2 As shown, the porous ceramic particles obtained in the present invention have a microsphere diameter of 1.2 mm.

[0035] The ceramic powder is alumina 99 ceramic with a D50 of 5μm.

[0036] The active diluent is dimethacrylate.

[0037] The photoinitiator is 2-hydroxy-2-methyl-1-phenylpropanone.

[0038] The modified silicon oxide is prepared by the following method: starch is configured into a starch aqueous solution with a concentration of about 15wt%, nano silicon oxide is put into 12 times the weight of the starch aqueous solution (i.e., the weight ratio of nano silicon oxide to starch aqueous solution is 1:12), stirred evenly so that the nano silicon oxide is fully coated with starch, fully dried at 65°C, and then ground into 200 mesh fine powder to obtain modified silicon oxide for standby use.

[0039] The photocurable oligomer is a modified epoxy acrylate oligomer, which is prepared by the following method: 36 parts of epoxy resin (E51) and 16.5 parts of ethanol are added to a reaction container, stirred to dissolve and heated to 120°C; 7.5 parts of lauryl methacrylate (BASF LMA 1214F) are added, stirred evenly, and then 0.58 parts of triphenylphosphine are added, and the reaction is carried out at a temperature of 125°C for 2 hours; the temperature is controlled at 108°C, 2.5 parts of hard monomer methyl methacrylate, 3.3 parts of soft monomer butyl acrylate, 6.7 parts of methoxy polyethylene glycol acrylate with a molecular weight of 750, and 0.56 parts of initiator azobisisobutyronitrile are mixed evenly, and then added dropwise to the reaction container at a uniform speed within 3 hours. After the reaction is completed, the mixture is kept warm for 2 hours, cooled to below 50°C and discharged to obtain a modified epoxy acrylate oligomer.

[0040] Example 2 A method for preparing porous ceramic particles comprises the following steps: (1) preparing a photocurable slurry: preparing 401 g, 312 g, 234 g, 5.1 g and 10 g of ceramic powder, photocurable oligomer, active diluent, photoinitiator and modified silicon oxide respectively, mixing and stirring them evenly to obtain a photocurable slurry; (2) importing a three-dimensional model of the porous ceramic particles into a 3D printing device to prepare a spherical ceramic body, wherein the 3D printing device is a sinking photocurable ceramic 3D printer; (3) treating the spherical ceramic body, heating it to 600°C at a heating rate of about 7°C / min, and keeping it warm for 1.5 hours, thereby removing organic components in the spherical ceramic body to form micropores; (4) sintering the treated spherical ceramic body, heating it to 1700°C at a heating rate of about 10°C / min, and keeping it warm for 2 hours to obtain porous ceramic particles, wherein the obtained porous ceramic particles are microspheres with a diameter of 1.2 mm.

[0041] The ceramic powder is alumina 99 ceramic with a D50 of 6μm.

[0042] The active diluent is trimethacrylate.

[0043] The photoinitiator is 1-hydroxycyclohexyl phenyl ketone.

[0044] The modified silicon oxide is prepared by the following method: starch is configured into a starch aqueous solution with a concentration of about 15wt%, nano silicon oxide is put into 10 times the weight of the starch aqueous solution (i.e., the weight ratio of nano silicon oxide to starch aqueous solution is 1:10), stirred evenly so that the nano silicon oxide is fully coated with starch, fully dried at 65°C, and then ground into 200 mesh fine powder to obtain modified silicon oxide for standby use.

[0045] The photocurable oligomer is a modified epoxy acrylate oligomer, which is prepared by the following method: 37 parts of epoxy resin (E20) and 18 parts of butanol are added into a reaction container, stirred to dissolve and heated to 120°C; 7.5 parts of lauryl methacrylate (BASF LMA 1214F) are added, stirred evenly, and then 0.61 parts of triphenylphosphine are added, and the reaction is carried out at a temperature of 118°C for 2 hours; the temperature is controlled at 106°C, 2.8 parts of hard monomer methyl methacrylate, 3.5 parts of soft monomer butyl acrylate, 6.8 parts of methoxy polyethylene glycol acrylate with a molecular weight of 1000, and 0.51 parts of initiator benzoyl peroxide are mixed evenly, and then added dropwise to the reaction container at a uniform speed within 3 hours. After the reaction is completed, the mixture is kept warm for 2 hours, cooled to below 50°C and discharged to obtain a modified epoxy acrylate oligomer.

[0046] Example 3 A method for preparing porous ceramic particles comprises the following steps: (1) preparing a photocurable slurry: preparing 498 g, 387 g, 300 g, 24 g and 98 g of ceramic powder, photocurable oligomer, active diluent, photoinitiator and modified silicon oxide respectively, mixing and stirring them evenly to obtain a photocurable slurry; (2) importing a three-dimensional model of the porous ceramic particles into a 3D printing device to prepare a spherical ceramic body, wherein the 3D printing device is a sinking photocurable ceramic 3D printer; (3) treating the spherical ceramic body, heating it to 550°C at a heating rate of 8°C / min, and keeping it warm for 2 hours, thereby removing organic components in the spherical ceramic body to form micropores; (4) sintering the treated spherical ceramic body, heating it to 1650°C at a heating rate of about 9°C / min, and keeping it warm for 2 hours to obtain porous ceramic particles, wherein the obtained porous ceramic particles are microspheres with a diameter of 1.2 mm.

[0047] The ceramic powder is alumina 99 ceramic with a D50 of 8μm.

[0048] The active diluent is trimethacrylate.

[0049] The photoinitiator is 1-hydroxycyclohexyl phenyl ketone.

[0050] The modified silicon oxide is prepared by the following method: starch is configured into a starch aqueous solution with a concentration of about 15wt%, nano silicon oxide is put into 15 times the weight of the starch aqueous solution (i.e., the weight ratio of nano silicon oxide to starch aqueous solution is 1:15), stirred evenly so that the nano silicon oxide is fully coated with starch, fully dried at 65°C, and then ground into 200 mesh fine powder to obtain modified silicon oxide for standby use.

[0051] The photocurable oligomer is a modified epoxy acrylate oligomer, which is prepared by the following method: 38.6 parts of epoxy resin (E44) and 16 parts of ethylene glycol butyl ether are added to a reaction container, stirred to dissolve and heated to 105°C; 7.7 parts of lauryl methacrylate (BASF LMA 1214F) are added, stirred evenly, and then 0.67 parts of triphenylphosphine are added, and the reaction is carried out at a temperature of 115°C for 2 hours; the temperature is controlled at 105°C, 2.1 parts of hard monomer vinyl acetate, 3.9 parts of soft monomer butyl methacrylate, 6.8 parts of methoxy polyethylene glycol acrylate with a molecular weight of 600, and 0.58 parts of initiator azobisisobutyronitrile are mixed evenly, and then added dropwise to the reaction container at a uniform speed within 3 hours. After the reaction is completed, the mixture is kept warm for 2 hours, cooled to below 50°C and discharged to obtain a modified epoxy acrylate oligomer.

[0052] Example 4 A method for preparing porous ceramic particles comprises the following steps: (1) preparing a photocurable slurry: preparing 409 g, 355 g, 223 g, 6.5 g and 18 g of ceramic powder, photocurable oligomer, active diluent, photoinitiator and modified silicon oxide respectively, mixing and stirring them evenly to obtain a photocurable slurry; (2) importing a three-dimensional model of the porous ceramic particles into a 3D printing device to prepare a spherical ceramic body, wherein the 3D printing device is a sinking photocurable ceramic 3D printer; (3) treating the spherical ceramic body, heating it to 500°C at a heating rate of about 9°C / min, and keeping it warm for 2 hours, thereby removing organic components in the spherical ceramic body to form micropores; (4) sintering the treated spherical ceramic body, heating it to 1900°C at a heating rate of about 14°C / min, and keeping it warm for 1 hour to obtain porous ceramic particles, wherein the obtained porous ceramic particles are microspheres with a diameter of 1.2 mm.

[0053] The ceramic powder is alumina 99 ceramic with a D50 of 4μm.

[0054] The active diluent is diisoacrylate.

[0055] The photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

[0056] The modified silicon oxide is prepared by the following method: starch is configured into a starch aqueous solution with a concentration of about 15wt%, nano silicon oxide is put into 10 times the weight of the starch aqueous solution (i.e., the weight ratio of nano silicon oxide to starch aqueous solution is 1:10), stirred evenly so that the nano silicon oxide is fully coated with starch, fully dried at 65°C, and then ground into 200 mesh fine powder to obtain modified silicon oxide for standby use.

[0057] The photocurable oligomer is a modified epoxy acrylate oligomer, which is prepared by the following method: 36.4 parts of epoxy resin (E44) and 17 parts of isopropanol are added to a reaction container, stirred to dissolve and heated to 105°C; 9.7 parts of lauryl methacrylate (BASF LMA 1214F) are added, stirred evenly, and then 0.67 parts of triphenylphosphine are added, and the reaction is carried out at a temperature of 115°C for 2 hours; the temperature is controlled at 105°C, 3.3 parts of hard monomer methyl methacrylate, 4.2 parts of soft monomer butyl methacrylate, 6.7 parts of methoxy polyethylene glycol acrylate with a molecular weight of 1000, and 0.55 parts of initiator tert-butyl perbenzoate are mixed evenly, and then added dropwise to the reaction container at a uniform speed within 3 hours. After the reaction is completed, the mixture is kept warm for 2 hours, cooled to below 50°C and discharged to obtain a modified epoxy acrylate oligomer.

[0058] Example 5 A method for preparing porous ceramic particles comprises the following steps: (1) preparing a photocurable slurry: preparing 489 g, 340 g, 220 g, 6.5 g and 32 g of ceramic powder, photocurable oligomer, active diluent, photoinitiator and modified silicon oxide respectively, mixing and stirring them evenly to obtain a photocurable slurry; (2) importing a three-dimensional model of the porous ceramic particles into a 3D printing device to prepare a spherical ceramic body, wherein the 3D printing device is a sinking photocurable ceramic 3D printer; (3) treating the spherical ceramic body, heating it to 550°C at a heating rate of about 7.5°C / min, and keeping it warm for 2 hours, thereby removing organic components in the spherical ceramic body to form micropores; (4) sintering the treated spherical ceramic body, heating it to 1850°C at a heating rate of about 9°C / min, and keeping it warm for 2 hours to obtain porous ceramic particles, wherein the obtained porous ceramic particles are microspheres with a diameter of 1.2 mm.

[0059] The ceramic powder is alumina 99 ceramic with a D50 of 10μm.

[0060] The active diluent is diisoacrylate.

[0061] The photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

[0062] The modified silicon oxide is prepared by the following method: starch is configured into a starch aqueous solution with a concentration of about 15wt%, nano silicon oxide is put into 10 times the weight of the starch aqueous solution (i.e., the weight ratio of nano silicon oxide to starch aqueous solution is 1:10), stirred evenly so that the nano silicon oxide is fully coated with starch, fully dried at 65°C, and then ground into 200 mesh fine powder to obtain modified silicon oxide for standby use.

[0063] The photocurable oligomer is a modified epoxy acrylate oligomer, which is prepared by the following method: 36.6 parts of epoxy resin (E20) and 18 parts of ethanol are added to a reaction container, stirred to dissolve and heated to 115°C; 7.5 parts of lauryl methacrylate (BASF LMA 1214F) are added, stirred evenly, and then 0.9 parts of triphenylphosphine are added, and the reaction is carried out at a temperature of 115°C for 2 hours; the temperature is controlled at 105°C, 3.2 parts of hard monomer methacrylate, 3.7 parts of soft monomer butyl methacrylate, 7.2 parts of methoxy polyethylene glycol acrylate with a molecular weight of 1000, and 0.54 parts of initiator tert-butyl hydroperoxide are mixed evenly, and then added dropwise to the reaction container at a uniform speed within 3 hours. After the reaction is completed, the mixture is kept warm for 2 hours, cooled to below 50°C and discharged to obtain a modified epoxy acrylate oligomer.

[0064] Example 6 A method for preparing porous ceramic particles comprises the following steps: (1) preparing a photocurable slurry: preparing 422 g, 355 g, 262 g, 6.8 g and 35 g of ceramic powder, photocurable oligomer, active diluent, photoinitiator and modified silicon oxide respectively, mixing and stirring them evenly to obtain a photocurable slurry; (2) importing a three-dimensional model of the porous ceramic particles into a 3D printing device to prepare a spherical ceramic body, wherein the 3D printing device is a sinking photocurable ceramic 3D printer; (3) treating the spherical ceramic body, heating it to 550°C at a heating rate of about 6.5°C / min, and keeping it warm for 2 hours, thereby removing organic components in the spherical ceramic body to form micropores; (4) sintering the treated spherical ceramic body, heating it to 1850°C at a heating rate of about 12°C / min, and keeping it warm for 2 hours to obtain porous ceramic particles, wherein the obtained porous ceramic particles are microspheres with a diameter of 1.2 mm.

[0065] The ceramic powder is alumina 99 ceramic with a D50 of 4μm.

[0066] The active diluent is trimethacrylate.

[0067] The photoinitiator is bisbenzoylphenylphosphine oxide.

[0068] The modified silicon oxide is prepared by the following method: starch is configured into a starch aqueous solution with a concentration of about 15wt%, nano silicon oxide is put into 10 times the weight of the starch aqueous solution (i.e., the weight ratio of nano silicon oxide to starch aqueous solution is 1:10), stirred evenly so that the nano silicon oxide is fully coated with starch, fully dried at 65°C, and then ground into 200 mesh fine powder to obtain modified silicon oxide for standby use.

[0069] The photocurable oligomer is a modified epoxy acrylate oligomer, which is prepared by the following method: 36.8 parts of epoxy resin (E21) and 19 parts of ethanol are added to a reaction container, stirred to dissolve and heated to 118°C; 7.2 parts of lauryl methacrylate (BASF LMA 1214F) are added, stirred evenly, and then 0.58 parts of triphenylphosphine are added, and the reaction is carried out at a temperature of 115°C for 2 hours; the temperature is controlled at 105°C, 3.3 parts of hard monomer vinyl acetate, 3.6 parts of soft monomer butyl methacrylate, 7 parts of methoxy polyethylene glycol acrylate with a molecular weight of 550, and 0.53 parts of initiator azobisisobutyronitrile are mixed evenly, and then added dropwise to the reaction container at a uniform speed within 3 hours. After the reaction is completed, the mixture is kept warm for 2 hours, cooled to below 50°C and discharged to obtain a modified epoxy acrylate oligomer.

[0070] Comparative Example 1 Compared with Example 1, the photocurable oligomer in the ingredients of the photocurable slurry is an acrylate oligomer (Sartomer CN996 NS resin), and the rest is the same as Example 1.

[0071] Comparative Example 2 Compared with Example 1, the ingredients of the photocurable slurry do not contain modified silicon oxide, and the modified silicon oxide is replaced by an equal amount of active diluent. The rest are the same as Example 1.

[0072] Comparative Example 3 Compared with Example 1, the modified silicon oxide was replaced with an equal amount of silicon oxide (Sumitomo Chemical AM-21), and the rest was the same as Example 1.

[0073] Comparative Example 4 Compared with Example 1, the modified silicon oxide was replaced by an equal amount of starch, and the rest was the same as Example 1.

[0074] Porous ceramic particle performance test The porous ceramic particles obtained in Examples 1-6 and Comparative Examples 1-4 were tested for performance, and the testing method was as follows: Porosity: Tested according to GB / T1966-1996 “Test method for apparent porosity and bulk density of porous ceramics”.

[0075] The porous ceramic particles prepared in the examples and comparative examples were used to form filter rods with acetate fiber bundles. When manufacturing cigarette filter rods, the pre-weighed ceramic particles and acetate fiber bundles were put into a mixer according to the addition ratio (the amount of porous ceramic particles doped was 15% of the total volume of the cigarette filter rod), and the two raw materials were fully mixed. The mixed raw materials were then sent to a filter rod forming machine. The formed filter rods were cured and dried, and finally wrapped with cigarette paper to obtain cigarette filter rods of corresponding specifications. Then, cigarettes were made with tobacco and the total particulate matter, tar content and nicotine content of the mainstream cigarette smoke were tested. The total particulate matter, tar content and nicotine content were measured with reference to GB / T19609-2004 conventional analysis smoking machine for cigarettes.

[0076] The preparation method of cigarette filter rod and tobacco into cigarette is a conventional operation in the art, and can be prepared by referring to the following steps: (1) 50 g of tobacco leaves and 100 g of tobacco stems purchased from Yunnan China Tobacco Industry Co., Ltd. were crushed into tobacco powder of 100-120 mesh at 40°C; (2) the tobacco powder is mixed with sodium bicarbonate, potassium citrate, 10% tobacco white latex solution, propylene glycol and tobacco flavoring material in a mass ratio of 100:1:0.5:5:0.2:0.05 to obtain tobacco particles by one step granulation and drying, and particles smaller than 70 mesh are removed by air separation; (3) Spraying polyethylene hot melt adhesive on the surface of the above-mentioned tobacco particles that have passed the air selection, pressing it from one end of a cylindrical mold with a diameter of 7.5 mm using a continuous feeding device under heat preservation conditions, and extruding it from the other end after solidification and rapid cooling to obtain a tobacco round rod with a density of 0.3 g / mL; (4) After the tobacco rod is extruded, it is wrapped with cigarette paper, cut into 59 mm lengths, and connected to the cigarette filter rod through tipping paper to form a cigarette.

[0077] The test results are shown in Table 1.

[0078] Table 1

[0079] It can be seen from Table 1 that the porous ceramic particles provided in the embodiments of the present invention have excellent porosity, significant filtering effects on total particulate matter, tar and nicotine, and can greatly reduce the content of harmful substances, while the performance of the products in the comparative examples is not as good as that in the embodiments.

[0080] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing porous ceramic particles, characterized in that: The following steps are involved: (1) Preparing a photocurable slurry: mixing and stirring a ceramic powder, a photocurable oligomer, a reactive diluent, a photoinitiator and modified silicon oxide in a weight ratio of (4-5): (3-4): (2-3): (0.05-0.25): (0.1-1) to obtain a photocurable slurry; (2) 3D printing the photocurable slurry to obtain a spherical ceramic body; (3) treating the spherical ceramic body to remove organic components in the spherical ceramic body to form micropores; (4) sintering the treated spherical ceramic body to obtain porous ceramic particles; Wherein, the diameter of the porous ceramic particles is 1-1.5 mm.

2. The method for preparing porous ceramic particles according to claim 1, characterized in that: In the step (1) photocurable slurry, the weight ratio of ceramic powder, photocurable oligomer, reactive diluent, photoinitiator and modified silicon oxide is 4.46:3.67:2.61:0.061:0.

45.

3. The method for preparing porous ceramic particles according to claim 1, characterized in that: The ceramic powder is aluminum oxide with a purity of more than 99.9%, and the D50 of the ceramic powder is 4 μm-10 μm.

4. The method for preparing porous ceramic particles according to claim 1, characterized in that: The photocurable oligomer is a modified epoxy acrylate oligomer, which is prepared by the following method: Step 1-1, add 36-38.6 parts of epoxy resin and 16-19 parts of solvent, stir to dissolve and heat to 105°C-120°C; Step 1-2, add 7.2-9.7 parts of long-chain alkyl ester from biological sources, stir evenly, add 0.58-0.9 parts of triphenylphosphine, and react at a temperature of 115° C.-125° C. for 2-3 hours; Step 1-3, the temperature is controlled between 105°C and 108°C, 2.1-3.3 parts of hard monomer, 3.3-4.2 parts of soft monomer, 6.7-7.2 parts of functional acrylic monomer, and 0.51-0.58 parts of initiator are mixed evenly, and added dropwise at a uniform speed for 2-3 hours. After the reaction is completed, keep warm for 2 hours, cool to below 50°C and discharge the material to obtain a modified epoxy acrylate oligomer.

5. The method for preparing porous ceramic particles according to claim 4, characterized in that: The bio-sourced long-chain alkyl ester is selected from one or more of cardanol acrylate, allyl glycidyl cardanol ether, glycidyl methacrylate cardanol ether, hydroxyethyl acrylate cardanol ether or lauryl methacrylate; and / or, the hard monomer is selected from one or more of methacrylic acid, methyl methacrylate or vinyl acetate; And / or, the soft monomer is butyl acrylate or butyl methacrylate; And / or, the functional acrylic monomer is methoxy polyethylene glycol acrylate; And / or, the solvent is a water-soluble alcohol ether solvent, selected from one or more of ethylene glycol butyl ether, butanol, isopropanol, sec-butanol, and ethanol; And / or, the initiator is a peroxide and / or an azo initiator, selected from one or more of benzoyl peroxide, tert-butyl hydroperoxide, tert-butyl perbenzoate, di-tert-butyl peroxide, and azobisisobutyronitrile.

6. The method for preparing porous ceramic particles according to claim 5, characterized in that: The molecular weight of the methoxy polyethylene glycol acrylate is 550-1000.

7. The method for preparing porous ceramic particles according to claim 1, characterized in that: The reactive diluent is selected from one or more of dimethacrylate, trimethacrylate, tetramethacrylate, diisoacrylate, trimethacrylate or triisoacrylate; And / or, the photoinitiator is one or more of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, bisbenzoylphenylphosphine oxide, and α-dimethoxy-α-phenylacetophenone.

8. The method for preparing porous ceramic particles according to claim 1, characterized in that: The modified silicon oxide is nano silicon oxide coated with starch, which is specifically prepared by the following method: starch is configured into a starch aqueous solution with a concentration of 10-20wt%, nano silicon oxide is added into the starch aqueous solution, stirred evenly so that the nano silicon oxide is fully coated with starch, and the modified silicon oxide is obtained after drying and grinding, wherein the weight ratio of the nano silicon oxide to the starch aqueous solution is 1: (10-15).

9. The method for preparing porous ceramic particles according to claim 1, characterized in that: The specific method of step (2) 3D printing the photocurable slurry is as follows: the three-dimensional model of the porous ceramic particles is introduced into a 3D printing device to prepare a spherical ceramic body. The 3D printing device can be a pull-up type or a sinking type photocurable ceramic 3D printer according to the needs.

10. The method for preparing porous ceramic particles according to claim 1, characterized in that: The step (3) of treating includes: heating to 450°C-600°C at a heating rate of 0.1°C / min-10°C / min, and keeping the temperature for 0.5h-10h.

11. The method for preparing porous ceramic particles according to claim 1, characterized in that: The sintering step in step (4) includes heating to 1650°C-1850°C at a heating rate of 0.5°C / min-20°C / min, and keeping the temperature for 0.5h-10h.

12. A porous ceramic particle prepared by the preparation method according to any one of claims 1 to 11, characterized in that: The porosity of the porous ceramic particles is 71.4%-77.8%.

13. A method for using the porous ceramic particles prepared by any one of claims 1 to 11 in preparing tobacco filters: The porous ceramic particles and the acetate fiber bundle are formed into filter rods.

14. A method for using the porous ceramic particles according to claim 13 in preparing a tobacco filter: The doping amount of the porous ceramic particles accounts for 15% of the total volume of the porous ceramic particles and the acetate fiber bundle.

Citation Information

Patent Citations

  • Adsorption filter bead applied to cigarette filter tip

    CN111227302A

Cited By

  • Gadolinium oxysulfide cold storage ceramic microspheres as well as preparation method and application thereof

    CN120817804A

  • Photocuring 3D printing aluminum oxide ceramic microbead as well as preparation method and application thereof

    CN121405445A